Kebijakan dividen memoderasi pengaruh struktur modal dan profitabilitas terhadap nilai perusahaan - Khafidhotul Ainiah; Dyah Ani Pangastuti (Jurnal Ilmiah Bisnis dan Perpajakan (Bijak), 2026)
This study aims to analyze the influence of capital structure and profitability on firm value, with dividend policy serving as a moderating variable, focusing on mining sector companies listed on the Indonesia Stock Exchange during the 2022–2024 period. A quantitative approach was employed using secondary data derived from annual financial reports. The sample was selected using a purposive sampling method, resulting in 19 companies and 57 observations. Data analysis was conducted using descriptive statistics, classical assumption tests, and Moderated Regression Analysis (MRA) with the aid of SPSS. The results indicate that capital structure does not have a significant effect on firm value, whereas profitability has a positive and significant effect on firm value. Dividend policy was found to have a significant effect on firm value. Furthermore, while dividend policy failed to moderate the influence of capital structure on firm value, it successfully moderated the influence of profitability on firm value. These findings suggest that dividend policy acts as a quasi-moderator in the relationship between profitability and firm value. The study is expected to contribute to the development of financial literature and serve as a reference for management and investors in financial decision-making.